Perancangan Sistem Informasi Percetakan Toko Denis Palembang Berbasis Web - Akhmad Sayuti; Irwansyah Irwansyah; Abdul Harist (Jurnal Nasional Ilmu Komputer, 2023)
The author made observations at Denis Palembang Printing Shop, in the printing press. The data processing has been computerized using a simple application, Microsoft Word and Microsoft Office, in processing data and making reports. To support several theories such as UML the data processing method used is the waterfall model. and AppServ software (Apache, MySql), PHP and MySQL, Microsoft Office and Microsoft Visio as supporting software. Web-based data processing will make it easier to process ordering data, goods data, customer data, payment data and making reports in Denis Palembang Shop Printing so that it can help employees at Denis Palembang Printing Shop process and make reports and other matters needed